Temperature influence on the repair of a hardfacing coating using laser metal deposition and assessment of the repair innocuity - Wilfried Pacquentin; Pierre Wident; Jérôme Varlet; Thomas Cailloux; Hicham Maskrot (Journal of Advanced Joining Processes)
Additive manufacturing (AM) is a proven time- and cost-effective method for repairing parts locally damaged after e.g. repetitive friction wear or corrosion. Repairing a hardfacing coating using AM technologies presents however several simultaneous challenges arising from the complex geometry and a high probability of crack formation due to process-induced stress. We address the repair of a cobalt-based Stellite™ 6 hardfacing coating on an AISI 316L substrate performed using Laser Powder Directed Energy Deposition (LP-DED) and investigate the influence of key process features and parameters. We describe our process which successfully prevents crack formation both during and after the repair, highlighting the design of the preliminary part machining phase, induction heating of an extended part volume during the laser repair phase and the optimal scanning strategy. Local characterization using non-destructive testing, Vickers hardness measurements and microstructural examinations by scanning electron microscopy (SEM) show an excellent metallurgical quality of the repair and its interface with the original part. In addition, we introduce an innovative process qualification test assessing the repair quality and innocuity, which is based on the global response to induced cracks and probes the absence of crack attraction by the repair (ACAR11 ACAR stands for absence of crack attraction by the repair.). Here this ACAR test reveals a slight difference in mechanical behavior between the repair and the original coating which motivates further work to eventually make the repair imperceptible.